2014
DOI: 10.4269/ajtmh.13-0285
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Vivax Malaria Acquired Before 20 Weeks of Pregnancy on Subsequent Changes in Fetal Growth

Abstract: Abstract. The resistance index (RI), pulsatility index (PI), fetal biometry, fetal heart rate (FHR), placental thickness, and hemoglobin levels were compared in 30 Plasmodium vivax-infected women between 14 and 20 weeks of pregnancy and a control group. Evaluations were performed at the moment of the malaria diagnosis and 26 weeks of pregnancy. The malaria group had lower levels of hemoglobin and greater placental thickness in both assessments, higher FHR in the first evaluation, and lower values on fetal biom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
37
0
13

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(50 citation statements)
references
References 40 publications
0
37
0
13
Order By: Relevance
“…Previous studies exploring the impact of timing of malaria infection during pregnancy have been mixed, and few prior studies have examined the relationship between timing of infection in pregnancy and development of placental malaria despite the well-established association of placental malaria with increased adverse obstetric outcomes. 10,19,20 Several studies have found increased rates of SGA, 21 decreased birthweight, 22,23 and decreased fetal growth velocity 24 with early malaria infection while others have found more significant detrimental effects on fetal growth with infection in the second or third trimesters 25 and/or at delivery. 26,27 Additionally, several studies found a negative impact on fetal growth with both early and late infection.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies exploring the impact of timing of malaria infection during pregnancy have been mixed, and few prior studies have examined the relationship between timing of infection in pregnancy and development of placental malaria despite the well-established association of placental malaria with increased adverse obstetric outcomes. 10,19,20 Several studies have found increased rates of SGA, 21 decreased birthweight, 22,23 and decreased fetal growth velocity 24 with early malaria infection while others have found more significant detrimental effects on fetal growth with infection in the second or third trimesters 25 and/or at delivery. 26,27 Additionally, several studies found a negative impact on fetal growth with both early and late infection.…”
Section: Discussionmentioning
confidence: 99%
“…A small number of ultrasound-based studies in LMICs have examined factors associated with abnormal placental development and fetal growth, and have evaluated the potential effects of malaria parasitaemia on uteroplacental and fetoplacental blood flow [1419]. Symptomatic falciparum malaria in early third trimester was associated with acutely increased UARI and reduced MCA resistance in French Guiana [14, 15].…”
Section: Introductionmentioning
confidence: 99%
“…Infection in early pregnancy (<20 gestational weeks) was associated with increased uterine artery resistance in undernourished Congolese women, and with reduced UARI in later pregnancy amongst primigravidae, the latter perhaps being due to adaptive villous angiogenesis following a treated infection [18]. In a case–control study of P. vivax in pregnancy in Brazil, parasitaemia early in pregnancy was associated with reduced fetal growth later in pregnancy, but UARI did not differ between infected/uninfected groups [19]. …”
Section: Introductionmentioning
confidence: 99%
“…Previous studies exploring the impact of timing of malaria infection during pregnancy have been mixed, and few prior studies have examined the relationship between timing of infection in pregnancy and development of placental malaria despite the well-established association of placental malaria with increased adverse obstetric outcomes [10,19,20]. Several studies have found increased rates of SGA [21], decreased birthweight [22,23], and decreased fetal growth velocity [24] with early malaria infection while others have found more signi cant detrimental effects on fetal growth with infection in the second or third trimesters [25] and/or at delivery [26,27].…”
Section: Discussionmentioning
confidence: 99%